2021
DOI: 10.1002/lsm.23403
|View full text |Cite
|
Sign up to set email alerts
|

Laser‐Assisted Hyaluronic Acid Delivery by Fractional Carbon Dioxide Laser in Facial Skin Remodeling: A Prospective Randomized Split‐Face Study in France

Abstract: Background and Objectives: Combining the efficacy of ablative fractional carbon dioxide lasers (AFXL) to laser-assisted hyaluronic acid delivery (LAHAD) has not yet been studied. The objective of our study was to evaluate the safety and the efficacy of laser-assisted hyaluronic acid (HA) delivery with AFXL in facial skin remodeling.Study Design/Materials and Methods: We conducted a prospective, double-blinded, randomized split-face study on 20 patients from 30 to 70 years old, with a skin phototype from I to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…Dermal remodeling induced by AFL is characterized by increased vascularity, a reduced senescent fibroblast population, and synthesis and remodeling of the extracellular matrix. 6 In a recent prospective randomized clinical trial, AFL resurfacing on aged skin resulted in a sustained reduction in the number of actinic keratosis and a decreased rate of non-melanoma skin cancers. 7 Despite strong clinical evidence of AFL efficacy with a variety of dermatological conditions, the mechanism by which AFL asserts its dermal remodeling effects is still largely unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dermal remodeling induced by AFL is characterized by increased vascularity, a reduced senescent fibroblast population, and synthesis and remodeling of the extracellular matrix. 6 In a recent prospective randomized clinical trial, AFL resurfacing on aged skin resulted in a sustained reduction in the number of actinic keratosis and a decreased rate of non-melanoma skin cancers. 7 Despite strong clinical evidence of AFL efficacy with a variety of dermatological conditions, the mechanism by which AFL asserts its dermal remodeling effects is still largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…An ablative fractional laser (AFL) generates arrays of thermally induced microinjuries, thereby inducing secondary dermal remodeling. Dermal remodeling induced by AFL is characterized by increased vascularity, a reduced senescent fibroblast population, and synthesis and remodeling of the extracellular matrix 6 . In a recent prospective randomized clinical trial, AFL resurfacing on aged skin resulted in a sustained reduction in the number of actinic keratosis and a decreased rate of non‐melanoma skin cancers 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Although the authors suggested that the microneedles of the FRMN can enable physical transdermal delivery of macromolecules with high molecular masses, they also questioned if the energy delivered by FRMN could potentially lead to early destruction of the PLA in the protocol of topical PLA followed by FRMN. Finally, Benzaquen and colleagues 9 used another modified method of fractional CO 2 laser-assisted topical hyaluronic acid (instead of PLLA) delivery for rejuvenation. Immediately after treatment with fractional CO 2 laser (MiXto SX; Lasering s.r.l, Moderna, Italy; spot size 300 μm, power 10 W, density 5%, index 8), 1 mL hyaluronic acid gel (Restylane Skinboosters Vital; Galderma, La Tour-de-Peilz, Switzerland) without lidocaine, 100 to 500 μm) was applied on one hemiface and saline was applied on the other hemiface.…”
Section: Discussionmentioning
confidence: 99%
“…8 A separate study used topical hyaluronic acid application after fractional CO 2 laser, resulting in facial rejuvenation. 9 Based on these preliminary reports, some clinicians have modified the method by using other physical modalities, such as FRMN, fractional nonablative laser, and microneedling to deliver various fillers. Despite the proliferation of use of these devices to assist in filler delivery, little is known about the optimal settings for laser-assisted or device-assisted filler delivery, especially regarding the type of devices and fillers and how effective these techniques are.…”
mentioning
confidence: 99%
See 1 more Smart Citation